Approximate Bayesian Computation of radiocarbon and paleoenvironmental record shows population resilience on Rapa Nui (Easter Island) - Robert J. DiNapoli (Nature Portfolio, 2021)
Summed probability distributions of radiocarbon dates can be used to estimate past demography, but methods to test for associations with environmental change are lacking. Here, DiNapoli et al. propose an approach using Approximate Bayesian Computation and illustrate it in a case study of Rapa Nui.